Nature-derived nanocellulose as a platform to modulate bioavailability of biomolecules in the gastrointestinal tract - Ho, Chin Guan (Nanyang Technological University, 2023)
Exploitation of nature-derived materials has become popular due to growing environmental concerns. Among these materials explored, cellulose is of particular interest because of its abundance, relative ease of access, and significant waste streams. Recently, cellulose nanofiber (CNF) has been proven to have the ability to modulate the digestion and absorption of lipids in a high-fat diet. The overarching hypothesis in this project is that CNF can be modified to modulate the bioavailability, digestion, and uptake of food ingredients and toxins in the GIT by forming inclusion complexes and promoting interacting with surface hydroxyl groups. The surface chemistry and surface properties of pristine CNF, obtained from wood pulp, were first characterized to build the fundamental knowledge for subsequent interaction studies. Next, CNF was successfully functionalized with (2-hydroxypropyl)-β-cyclodextrin (HPBCD) using citric acid (CA) as a crosslinker via esterification. Functionally, the potential for pristine and functionalized CNF (FCNF) to interact with boscalid was tested. In vitro simulated GIT platform was adopted to study the adsorption of boscalid on the CNF/FCNF in the GIT, as well as the interaction of nanocellulose in the presence of high-fat food model. FCNF was found to have a slightly better effect in binding boscalid and have greater effect in retarding the triglycerides (TG) digestion than CNF. Nano-isothermal calorimetry (Nano-ITC) was conducted to study the interaction of various compounds present in the GIT. Corona studies confirmed that remnant proteins and lipids are preserved as “hard corona” on the surface of CNF/FCNF. This project sought to demonstrate the substantial potential for CNF to be used as a modulation platform to mitigate food digestion and uptake in the GIT. It was found that FCNF had excellent performance in reducing fat absorption and higher removal rate of boscalid from human body. FCNF has great potential to be designed into a 2-in-1 dietary supplement with weight loss and pesticide removal purposes.